SUBGINGIVAL MICROBIOTA IN SEVERE CHRONIC PERIODONTITIS - Christina Popova; Velitchka Dosseva-Panova; Angelina Kisselova-Yaneva; Vladimir E. Panov (Peytchinski Publishing, 2014)
Literature data relate certain Gram-negative anaerobe microorganisms with advanced destructive periodontal lesion. There are some references which reported higher levels of periodontal pathogens by the red and orange complex in deep periodontal pockets. The aim of this study is to determine the presence of most important periodontal pathogens and Candida spp. in deep periodontal pockets in patients with severe chronic periodontitis. The results of this study indicate the presence of high levels of periodontal pathogens in a strong connection with periodontal disease in deep periodontal pockets of patients studied.